Vertical bipolar junction transistor triggered silicon‐controlled rectifier for nanoscale ESD engineering. Issue 7 (1st March 2020) - Du, Feibo; Hou, Fei; Song, Wenqiang; Xu, YiChen; Liu, Jizhi; Liu, Zhiwei; Liou, Juin J.
Abstract : In this Letter, a novel vertical bipolar junction transistor (BJT) triggered silicon‐controlled rectifier (VBTSCR) is proposed for advanced nanoscale electrostatic discharge (ESD) protection applications. With the help of a vertical NPN transistor in floating base configuration, the new silicon‐controlled rectifier (SCR) structure achieves lower trigger voltage and better clamping capacity than the prior enhanced modified lateral SCR (EMLSCR) under the same layout footprint. The ESD characteristics are measured using the transmission line pulsing tester. Compared with that of EMLSCR, the trigger voltage of VBTSCR drops by 1 V, and the effective ESD robustness of VBTSCR has been doubled significantly. Based on these advantages, the proposed VBTSCR can provide ESD protection for the advanced 1.8/2.5 V input/output circuits more efficiently.